Efficacy of bendamustine and rituximab in unfit patients with previously untreated chronic lymphocytic leukemia. Indirect comparison with ibrutinib in a real‐world setting. A GIMEMA‐ERIC and US study. (24th September 2020) - Cuneo, Antonio; Mato, Anthony R.; Rigolin, Gian Matteo; Piciocchi, Alfonso; Gentile, Massimo; Laurenti, Luca; Allan, John N.; Pagel, John M.; Brander, Danielle M.; Hill, Brian T.; Winter, Allison; Lamanna, Nicole; et al.
Abstract: Limited information is available on the efficacy of front‐line bendamustine and rituximab (BR) in chronic lymphocytic leukemia (CLL) with reduced renal function or coexisting conditions. We therefore analyzed a cohort of real‐world patients and performed a matched adjusted indirect comparison with a cohort of patients treated with ibrutinib. One hundred and fifty‐seven patients with creatinine clearance (CrCl) <70 mL/min and/or CIRS score >6 were treated with BR. The median age was 72 years; 69% of patients had ≥2 comorbidities and the median CrCl was 59.8 mL/min. 17.6% of patients carried TP53 disruption. The median progression‐free survival (PFS) was 45 months; TP53 disruption was associated with a shorter PFS ( P  = 0.05). The overall survival (OS) at 12, 24, and 36 months was 96.2%, 90.1%, and 79.5%, respectively. TP53 disruption was associated with an increased risk of death ( P  = 0.01). Data on 162 patients ≥65 years treated with ibrutinib were analyzed and compared with 165 patients ≥65 years treated with BR. Factors predicting for a longer PFS at multivariable analysis in the total patient population treated with BR and ibrutinib were age (HR 1.06, 95% CI 1.02‐1.10, P  < 0.01) and treatment with ibrutinib (HR 0.55, 95% CI 0.33‐0.93, P  = 0.03). In a post hoc analysis of patients in advanced stage, a significant PFS advantage was observed in patient who had received ibrutinib ( P  = 0.03), who showed a trend for OS advantage ( P  = 0.08). We arrived at the following conclusions: (a) BR is a relatively effective first‐line regimen in a real‐world population of unfit patients without TP53 disruption, (b) ibrutinib provided longer disease control than BR in patients with advanced disease stage. Abstract : Bendamustine and Rituximab was a relatively effective first‐line regimen in real‐world untreated CLL patients with reduced renal function or coexisting conditions without TP53 disruption.In a matched‐adjusted indirect comparison with a cohort of CLL patients treated upfront, ibrutinib provided longer PFS than bendamustine and rituximab in those with advanced stage.